2008
DOI: 10.1017/s1740925x09990123
|View full text |Cite
|
Sign up to set email alerts
|

nkx2.2apromotes specification and differentiation of a myelinating subset of oligodendrocyte lineage cells in zebrafish

Abstract: During development, multipotent neural precursors give rise to oligodendrocyte progenitor cells (OPCs), which migrate and divide to produce additional OPCs. Near the end of embryogenesis and during postnatal stages, many OPCs stop dividing and differentiate as myelinating oligodendrocytes, whereas others persist as nonmyelinating cells. Investigations of oligodendrocyte development in mice indicated that the Nkx2.2 transcription factor both limits the number of OPCs that are formed and subsequently promotes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 43 publications
6
73
0
4
Order By: Relevance
“…Although spatial patterning of the neural tube is known to be conserved in zebrafish (Guner and Karlstrom, 2007), the temporality of its establishment remains to be explored. We examined the expression time course of olig2 and nkx2.2, named nkx2.2a in zebrafish (Kucenas et al, 2008a), known to be differentially sensitive to Shh signaling levels in zebrafish (Barth and Wilson, 1995;Guner and Karlstrom, 2007;Park et al, 2002). As previously reported (Park et al, 2002), olig2 was expressed from 12 hpf (data not shown).…”
Section: Sulf1 Depletion Impairs Generation Of Opcs and V3 Interneuromentioning
confidence: 70%
“…Although spatial patterning of the neural tube is known to be conserved in zebrafish (Guner and Karlstrom, 2007), the temporality of its establishment remains to be explored. We examined the expression time course of olig2 and nkx2.2, named nkx2.2a in zebrafish (Kucenas et al, 2008a), known to be differentially sensitive to Shh signaling levels in zebrafish (Barth and Wilson, 1995;Guner and Karlstrom, 2007;Park et al, 2002). As previously reported (Park et al, 2002), olig2 was expressed from 12 hpf (data not shown).…”
Section: Sulf1 Depletion Impairs Generation Of Opcs and V3 Interneuromentioning
confidence: 70%
“…To further determine whether transgene expression occurred in oligodendrocytes, we crossed this fish with an already characterized line, olig2:DsRed, in which cytoplasmic DsRed is expressed under the control of the olig2 promoter in oligodendrocytes and specific neurons. In the spinal cord, dorsally migrating olig2:DsRed 1 cells have previously been identified as oligodendrocytes (Kucenas et al, 2008). Some of these were surrounded by a Claudin k-labeled GFP-positive membrane, which continued into processes that ended in longitudinal structures reminiscent of myelinated internodes (Fig.…”
Section: Generation Of Claudin K:gfp Transgenic Zebrafishmentioning
confidence: 91%
“…Some embryos were raised in the presence of 0.003% n-phenylthiourea from 20 hpf to prevent pigmentation. The following transgenic zebrafish lines were used: Tg(olig2:EGFP) (Shin et al, 2003), tg (olig2:DsRed2) (Kucenas et al, 2008). For simplicity, the olig2 transgenic lines are abbreviated as olig2:GFP and olig2:DsRed, respectively, in this article.…”
Section: Fish Raising and Husbandrymentioning
confidence: 99%
“…OPCs because previous studies demonstrate that OPCs express both nkx2.2a and olig2, and cells with this expression pattern are only ever observed within the CNS in wildtype larvae (Kucenas et al, 2008a). Once in the periphery, these ectopic OPCs migrated along motor axons until they ultimately associated with single axons and initiated ensheathment, as evidenced by the creation of thin, nkx2.2a + rectangular tubes (data not shown), a phenotype consistent with glial ensheathment/myelination (Czopka et al, 2013;Kucenas et al, 2009;Nawaz et al, 2015;Snaidero et al, 2014;Takada et al, 2010 (Figure 4-2D).…”
Section: Erbb3bmentioning
confidence: 99%
“…The nkx2.2a:megfp transgenic zebrafish line revealed that perineurial glial cells express nkx2.2a (Kucenas et al, 2008b). However, nkx2.2a is not specific to perineurial cells, and cells of the ventral floor plate, including OPCs, especially those of the myelinating oligodendrocyte fate (Kucenas et al, 2008a), also express nkx2.2a (Kitada & Rowitch, 2006;Kucenas et al, 2008a;Kuhlmann et al, 2008;Liu et al, 2007;Qi et al, 2001). …”
Section: Do Ectopic Oligodendrocytes Maintain Their Cns Profile and Cmentioning
confidence: 99%